Optimal Approximate Solution for Generalized Contraction Mappings - Komal, Somayya; Sultana, Nazra; Hussain, Azhar; Kumam, Poom (Communications in Mathematics and Applications, 2016)
In this paper, we obtain the best proximity point theorems for \(α\)-Geraghty contractions in the setting of complete metric spaces. We present some examples to prove the validity of our results. Our results extend and unify many existing results in the literature.